CD4+ T cell-derived IL-22 enhances liver metastasis by promoting angiogenesis - Zhang, Tao (2023)
Metastasis is a cancer-related systemic disease and is responsible for the greatest mortality rate among cancer patients. Interestingly, the interaction between the immune system and cancer cells seems to play a key role in metastasis formation in the target organ. However, this complex network is only partially understood. We previously found that IL-22 produced by tissue resident iNKT17 cells promotes cancer cell extravasation, the early step of metastasis. Based on these data, we aimed here to decipher the role of IL-22 in the last step of metastasis formation. We found that IL-22 levels were increased in established metastatic sites in both human and mouse. We also found that Th22 cells were the key source of IL-22 in established metastasis sites, and that deletion of IL-22 in CD4+ T cells was protective in liver metastasis formation. Accordingly, the administration of a murine IL-22 neutralizing antibody in the establishment of metastasis formation significantly reduced the metastatic burden in a mouse model. Mechanistically, IL-22-producing Th22 cells promoted angiogenesis in established metastasis sites. In conclusion, our findings highlight that IL-22 is equally as important in contributing to metastasis formation at late metastatic stages, and thus, identify it as a novel therapeutic target in established metastasis.